2021
DOI: 10.1093/ofid/ofab219
|View full text |Cite
|
Sign up to set email alerts
|

Peer Mobilization and Human Immunodeficiency Virus (HIV) Partner Notification Services Among Gay, Bisexual, and Other Men Who Have Sex With Men and Transgender Women in Coastal Kenya Identified a High Number of Undiagnosed HIV Infections

Abstract: Introduction HIV partner notification services (HPN), peer mobilisation with HIV self-testing and acute and early HIV infection (AEHI) screening among gay, bisexual, other men who have sex with men (GBMSM) and transgender women (TGW) were assessed for acceptability, feasibility and linkage to antiretroviral therapy (ART) and pre-exposure prophylaxis (PrEP) services. Methods Between April-August 2019, peer mobilisers mobilised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 38 publications
1
26
1
Order By: Relevance
“…HIV prevalence among TGW is estimated to be approximately 14.2%, which is higher compared to other vulnerable populations such as gay, bisexual, and other men who have sex with men (10.6%) [ 19 , 20 , 21 ]. Additionally, a similar trend is observed for TGW in the Middle East and North Africa, where infection rates continue to rise [ 5 , 9 ]. However, results from a study in São Paulo, Brazil, indicate an even higher prevalence of HIV among TGW compared to data from around the world [ 2 , 22 ].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…HIV prevalence among TGW is estimated to be approximately 14.2%, which is higher compared to other vulnerable populations such as gay, bisexual, and other men who have sex with men (10.6%) [ 19 , 20 , 21 ]. Additionally, a similar trend is observed for TGW in the Middle East and North Africa, where infection rates continue to rise [ 5 , 9 ]. However, results from a study in São Paulo, Brazil, indicate an even higher prevalence of HIV among TGW compared to data from around the world [ 2 , 22 ].…”
Section: Introductionsupporting
confidence: 59%
“…They are a diverse group of people who were assigned male sex at birth but mostly identify as women, trans women, and/or transfeminine. They are estimated to be more than 48 times more likely to be infected with HIV than cis women (those whose gender identity matches that assigned at birth) of reproductive age [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Transgender women of color in particular face high rates of infection and low use of important HIV prevention tools [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research with MSM continued uninterrupted for another 10 years, until complications related to the COVID pandemic later closed services. Increasingly, research was done in collaboration with LGBT groups and peer mobilisers, including an intervention trial that aimed to improve adherence to antiretroviral therapy among MSM, 116 a partner notification study that aimed to identify new HIV infections among MSM, 117 an intermittent pre-exposure prophylaxis study, 118 and the first known study to suggest that anti-MSM prejudice can be reduced among Kenyan health-care providers after sensitivity training. 119 Research with MSM was enabled through the strong support for vulnerable populations, the non-judgemental attitudes of research programme staff, and a strong community stakeholder engagement programme.…”
Section: Key Messagesmentioning
confidence: 99%
“…Local KP CSO involvement was critical to success as it ensured a trusted member of the community was bringing services. Other studies using similar peer navigation networks to reach the community have also demonstrated success [30, 31].…”
Section: Discussionmentioning
confidence: 99%